Renal Delivery of Pharmacologic Agents During Machine Perfusion to Prevent Ischaemia-Reperfusion Injury: From Murine Model to Clinical Trials - Franzin, Rossana; Stasi, Alessandra; Fiorentino, Marco; Simone, Simona; Oberbauer, Rainer; Castellano, Giuseppe; Gesualdo, Loreto (Frontiers in Immunology, 2021)
Donor organ shortage still remains a serious obstacle for the access of wait-list patients to kidney transplantation, the best treatment for End-Stage Kidney Disease (ESKD). To expand the number of transplants, the use of lower quality organs from older ECD or DCD donors has become an established routine but at the price of increased incidence of Primary Non-Function, Delay Graft Function and lower-long term graft survival. In the last years, several improvements have been made in the field of renal transplantation from surgical procedure to preservation strategies. To improve renal outcomes, research has focused on development of innovative and dynamic preservation techniques, in order to assess graft function and promote regeneration by pharmacological intervention before transplantation. This review provides an overview of the current knowledge of these new preservation strategies by machine perfusions and pharmacological interventions at different timing possibilities: in the organ donor, ex-vivo during perfusion machine reconditioning or after implementation in the recipient. We will report therapies as anti-oxidant and anti-inflammatory agents, senolytics agents, complement inhibitors, HDL, siRNA and H2S supplementation. Renal delivery of pharmacologic agents during preservation state provides a window of opportunity to treat the organ in an isolated manner and a crucial route of administration. Even if few studies have been reported of transplantation after ex-vivo drugs administration, targeting the biological pathway associated to kidney failure (i.e oxidative stress, complement system, fibrosis) might be a promising therapeutic strategy to improve the quality of various donor organs and expand organ availability.